Estimating Chilling and Growing Degree Hours Related to Deciduous Fruit Production in Kurdistan Region-Iraq - Ibrahim Maaroof Noori (Kufa Journal for Agricultural Sciences)
This study was carried out to estimate the annual chilling and heat accumulation in Kurdistan region-Iraq using three different models; chilling hours (CH), chilling units (CU) and chilling portions (CP), as well as estimating the accumulated growing degree hours (GDH) using the ChillR Package, Version 0.72.8 based on daily maxima and minima temperatures of 170 locations for 40 years (1983-2022) downloaded from NASA. The results showed that in Kurdistan region, the chilling hours with 7 classes ranged from 335 CH in Shahreban (Diyala) to 1083 CH in Amedi, Deraluk, Dinarte, Kani Masi, and Shiladize (Duhok), and Barzan (Erbil), with an average of 886 CH. The chilling units (CU, Utah Model) with 6 classes ranged from 507 CU (Shahreban, Diyala) to 1135 CU (Hizawa, Duhok), with an average of 927 CU. However, the chilling portions with 7 classes ranged from 30.0 CP in Shahreban to 58.3 CP in Ahmad Awa, Khurmal, Penjwin, Sirwan, and Zalm (Salaymaniyah), with an average of 49.5 CP. Growing degree hours with 7 classes ranged from 1136 GDH Choman, Galala, Haji Omaran and Samilan (Erbil) to 8564 GDH in Shahreban, with an average of 3256 GDH. All models were strongly correlated with location parameters, the highest strong correlations were found between each CP and GDH with AAT. The observations emphasized that both CU and CP models are more accurate than CH model for estimation of chilling and growing degree hours (units) in Kurdistan region-Iraq.